Encyclopedia of herbs & their uses - Bown, Deni (Distributed by Houghton Mifflin, 2002)
Full of information on cultivation, propagation and harvesting, this book covers both the practical uses and the history of herbs from around the world. It provides a comprehensive A-Z of herbs, with cultivation, propagation and harvesting information. It includes features on beneficial properties, including culinary, medicinal and commercial uses as well as warning symbols to alert you to potentially toxic or harmful herbs.